Pengaruh Kepemimpinan, Kepuasan Kerja Dan Lingkungan Kerja Terhadap Kinerja Karyawan Pada Cv. Ilmu Tetap Abadi Di Surakarta - Sari, Aprilita Mulya Kumala, Basworo Dibyo, S.E,M.Si (2016)
The purpose of this study was to determine the effect of leadership, job satisfaction and work environment on employee performance CV. Fixed science Abadi in Surakarta. The study also aimed to determine the effect of three independent variables on the dependent variable. In this study took a sample of 30 employees with engineering Sample Saturated ie sampling technique when all members of the population used as a sample, or research to make generalizations with a very small error. Another term saturated sample census, in which members of the population sampled (Sugiono, 2005: 96).Test instrument used in this study is Test Validity and Test Reliability. Then do the Classical Assumption Test form Normality Test, Test Multicolinearity, and Test heterocedastity. Hypothesis Testing in the form of multiple linear regression analysis used t test, F test, the coefficient of determination (R2). Based on this research t test shows that the leadership variables significantly influence employee performance a value of t= 2.401> table= 2.056 then Ho is rejected Ha accepted, job satisfaction variables significantly influence employee performance with a value of t = 2,355> t table= 2.056 then Ho is rejected Ha received, work environment variables significantly influence employee performance with a value of t= 2.645>table= 2.056 then Ho is rejected Ha accepted.